Becoming a primary physical educator. Issue 2 (17th February 2020) - Randall, Vicky
ABSTRACT: Previous studies have reported that generalist primary teachers lack the confidence and competence to teach Physical Education (PE). In response, schools have outsourced PE to external providers. This paper examines data from an online survey of 175 pre-service teachers (PSTs) in England and their perceived confidence to teach primary PE. Findings showed PSTs had high levels of confidence across a breadth of knowledge areas, specifically in areas relating to lesson planning, health and fitness and the subject's aims. Conversely, knowledge confidence was lowest in swimming, assessment and working with external providers. This paper argues that to address teacher confidence in PE, teachers must be positioned back as the main curriculum deliverers. An outcome of this research has been the development of a professional knowledge model for primary PE which recognises a breadth of professional knowledge needed to become a primary physical educator.